2019
DOI: 10.3892/ijmm.2019.4398
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 promotes TNF‑α‑induced chondrocyte death and migration injury via activating the�AMPK/Drp1/mitochondrial fission pathway

Abstract: Nuclear receptor subfamily 4 group A member 1 (NR4A1)-induced chondrocyte death plays a critical role in the development of osteoarthritis through poorly defined mechanisms. The present study aimed to investigate the role of NR4A1 in regulating chondrocyte death in response to tumor necrosis factor-α (TNF-α) and cycloheximide (cHX) treatment, with a focus on mitochondrial fission and the AMP-activated protein kinase (AMPK) signaling pathway. The results demonstrated that NR4A1 was significantly upregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The α subunit of AMPK exists in two isoforms in the mammalian, including AMPKα1 and AMPKα2, where both serve as catalytic subunits [40]. Increased NR4A1 acts on the AMPK/dynaminrelated protein 1 (Drp1) pathway to trigger mitochondrial ssion, leading to mitochondrial permeability transition pore related chondrocyte cell death [41]. Such results are consistent with that of the present study and highlight the credibility of the enrichment analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The α subunit of AMPK exists in two isoforms in the mammalian, including AMPKα1 and AMPKα2, where both serve as catalytic subunits [40]. Increased NR4A1 acts on the AMPK/dynaminrelated protein 1 (Drp1) pathway to trigger mitochondrial ssion, leading to mitochondrial permeability transition pore related chondrocyte cell death [41]. Such results are consistent with that of the present study and highlight the credibility of the enrichment analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Shi et al (2017) found that the upregulated NR4A1 in OA was mostly located in mitochondria and knockdown of NR4A1 could decrease the cleaved PARP1 expression and avoid apoptosis of OA chondrocytes. Zheng et al (2020) also revealed that NR4A1 promotes TNF-α-induced chondrocyte death via activating mitochondrial fission. These reports seemed to indicate that NR4A1 acted as a harmful factor in OA.…”
Section: Discussionmentioning
confidence: 89%
“… Terkeltaub et al (2011) suggest that AMPK restrained matrix degradation in chondrocytes in the presence of inflammatory cytokines IL-1β and tumor necrosis factor α (TNF-α) in both human and mouse ( Figure 3I ). Zheng et al (2020) showed that activation of AMPK/Drp1/mitochondrial fission pathway mediates chondrocyte death and migration injury ( Figure 3I ). Moreover, AMPK participated in chondrocyte dysfunction, hypertrophy, and fibrotic differentiation ( Liu N. et al, 2020 ; Liu Z. et al, 2020 ).…”
Section: Ampk In Chondrocytesmentioning
confidence: 99%